2013
DOI: 10.5812/ircmj.10930
|View full text |Cite
|
Sign up to set email alerts
|

Historical Cohort Study on the Factors Affecting Blood Pressure in Workers of Polyacryl Iran Corporation Using Bayesian Multilevel Modeling with Skew T Distribution

Abstract: BackgroundHypertension is considered as a major public health problem in most countries due to its association with ischemic heart disease which causes cerebrovascular disease and death.ObjectivesThe purpose of the present study was to study factors affecting Blood Pressure (BP).Patients and MethodsThe data were extracted from annual observation of the workers who worked in Polyacryl Iran Corporation (PIC) between 1998 and 2010. In this research, we assessed the effect of Body Mass Index (BMI), age, sex, job s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…For example, Gholami et al reported that the BMI of shift workers was less than day workers while in similar studies, shift workers were found to be more obese than day workers. They reviewed the process of hiring workers and stated that healthier people were recruited more for shift work than day work ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gholami et al reported that the BMI of shift workers was less than day workers while in similar studies, shift workers were found to be more obese than day workers. They reviewed the process of hiring workers and stated that healthier people were recruited more for shift work than day work ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to model and estimate the number of deaths in the absence of COVID-19 pandemic, the multilevel Poisson model was applied. Lower type one error and higher efficiency are two advantages of multilevel models in comparison with conventional models in the comparison of correlated data (9).…”
Section: Discussionmentioning
confidence: 99%
“…Chi-square test, NOVA, Kruskal-Wallis test and Bayesian multilevel modeling with skew t-distribution is used to find out any relationship between SW and BP adjusted for age, work experience, marital status and education. Prior distributions and statistical methodology were discussed in works Gholami et al 18 in this paper, P < 0.05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%